Neuraminidase inhibitor susceptibility and neuraminidase enzyme kinetics of human influenza A and B viruses circulating in Thailand in 2010-2015. - Nipaporn Tewawong; Bindumadhav M Marathe; Yong Poovorawan; Sompong Vongpunsawad; Richard J Webby; Elena A Govorkova (PLoS ONE, 2018)
Amino acid substitutions within or near the active site of the viral neuraminidase (NA) may affect influenza virus fitness. In influenza A(H3N2) and B viruses circulating in Thailand between 2010 and 2015, we identified several NA substitutions that were previously reported to be associated with reduced inhibition by NA inhibitors (NAIs). To study the effect of these substitutions on the enzymatic properties of NA and on virus characteristics, we generated recombinant influenza viruses possessing either a wild type (WT) NA or an NA with a single I222V, S331G, or S331R substitution [in influenza A(H3N2) viruses] or a single D342S, A395T, A395V, or A395D NA substitution (in influenza B viruses). We generated recombinant (7:1) influenza A and B viruses on the genetic background of A/Puerto Rico/8/1934 (A/PR/8, H1N1) or B/Yamanashi/166/1998 (B/YAM) viruses, respectively. In contrast to the expected phenotypes, all the recombinant influenza A(H3N2) and B viruses carrying putative NA resistance substitutions were susceptible to NAIs. The Km and Vmax for the NAs of A/PR8-S331G and A/PR8-S331R viruses were higher than for the NA of WT virus, and the corresponding values for the B/YAM-D342S virus were lower than for the NA of WT virus. Although there was initial variation in the kinetics of influenza A and B viruses' replication in MDCK cells, their titers were comparable to each other and to WT viruses at later time points. All introduced substitutions were stable except for B/YAM-D342S and B/YAM-A395V which reverted to WT sequences after three passages. Our data suggest that inferring susceptibility to NAIs based on sequence information alone should be cautioned. The impact of NA substitution on NAI resistance, viral growth, and enzymatic properties is viral context dependent and should be empirically determined.